(untitled) (Discourse of Law and Administration, 2021)
The study is focused on the analysis of selected issues concerning precinct election commissions. These bodies, despite being the lowest in the hierarchy of electoral bodies, are among the most identifiable and identified with the election process by voters among the entire election administration. It does not seem an exaggeration to say that they are critical to this process because the manner and level of their functioning largely translate into the perception of entire elections by society. Therefore, they play a significant role in the social legitimacy of the authorities elected as a result of elections. The choice of the discussed subject area is also justified by the high frequency and scope of amendments to this matter in recent years and the controversy accompanying these amendments. The analysis also covers the method of appointing precinct election commissions and their composition. The issue of the legitimacy of regulations defining entities authorised to nominate candidates to these committees and the consequences of these solutions, which is not often touched upon in the literature, has been discussed. Dilemmas related to the training of members of precinct election commissions have been presented. Reference was made to the previous solutions applicable before the implementation of the Election Code, to the arguments presented during the legislative process in this subject area, to the views of academic writers, as well as the opinions of NGOs and local government associations. The emerging reform proposals in this area have also been referred to and de lege ferenda conclusions have been formulated.